2016
DOI: 10.1111/jocd.12260
|View full text |Cite
|
Sign up to set email alerts
|

Combination of glycolic acid peel and topical 20% azelaic acid cream in melasma patients: efficacy and improvement in quality of life

Abstract: GA peel enhances therapeutic efficacy of topical AA cream for treatment of melasma, with improvement in quality of life without serious side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 11 publications
(16 reference statements)
0
11
0
2
Order By: Relevance
“…Amongst the various peels, glycolic acid (GA) has been most extensively studied in the treatment of melasma. A small open-label study found that 30–50% GA peels at 3-week intervals for 6 months in addition to AA 20% twice-daily regimen resulted in superior MASI scores when compared to AA 20% alone [ 45 ]. However, a small split-face study found no difference in decreased pigmentation when using HQ 4% with GA 20–30% compared to HQ alone [ 85 ].…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the various peels, glycolic acid (GA) has been most extensively studied in the treatment of melasma. A small open-label study found that 30–50% GA peels at 3-week intervals for 6 months in addition to AA 20% twice-daily regimen resulted in superior MASI scores when compared to AA 20% alone [ 45 ]. However, a small split-face study found no difference in decreased pigmentation when using HQ 4% with GA 20–30% compared to HQ alone [ 85 ].…”
Section: Introductionmentioning
confidence: 99%
“…Incluyó Los peelings superficiales con AG, AS y TCA deberían considerarse tratamientos de segunda línea. Los peelings con AG al 35% pueden ser útiles en el tratamiento del melasma [28]; Sarkar et al [29] mostraron que los peelings de AG 35% y salicílico-mandélico 20% pueden mejorar el melasma en pieles oscuras, y Dayal et al [30] alcanzaron resultados prometedores combinando AG (30-50%) y AA. Las exfoliaciones con TCA combinadas con solución de Jessner podrían ser una alternativa prometedora en el tratamiento del melasma recalcitrante, pero se necesitan estudios de mayor tamaño muestral [31].…”
Section: Discussionunclassified
“…However, clinical experience of combination of GA peel with azelaic acid in melasma is very limited [12]. Azelaic acid is a depigmenting agent which acts by inhibition of DNA synthesis and mitochondrial enzymes, thereby inducing direct cytotoxic effects on melanocytes.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the reason that in our case, we used only AA cream with serial GA peel, while in Erbil et al's study, they have used AA cream with 0.1% adapalene gel in combination with serial GA peel [2]. Thus, the use of additional topical agent, that is, adapalene 0.1% gel which acts in lightening of melasma by accelerating skin turnover and enhancing the efficacy of bleaching agents, may be responsible not only for higher percentage decrease in MASI score but also in side effects like erythema, pruritus, and post inflammatory hyperpigmentation (PIH) [7,12].…”
Section: Discussionmentioning
confidence: 99%